Solve for x :
x = 1 + 2 1 + 3 1 + 4 1 + 5 1 + ⋯
Note: If you think you know this problem so well, try this .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
good approach
Good thinking
Ramanujan's formula (eqn. 26) on nested radical:
u + n + a = a u + ( n + a ) 2 + u a ( u + n ) + ( n + a ) 2 + ( u + n ) a ( u + 2 n ) + ( n + a ) 2 + ( u + 2 n ) ⋯
Putting u = 2 , n = 1 and a = 0 , we have:
2 + 1 + 0 ⟹ x = 1 + 2 1 + 3 1 + 4 1 + 5 1 + ⋯ = 3
Problem Loading...
Note Loading...
Set Loading...
L e t , f ( n ) = n ( n + 2 ) f ( n ) f ( n ) = n ( n + 2 ) putting n = 1 we get x , x = f ( 1 ) = 1 ( 1 + 2 ) 3 = n ( n + 2 ) 2 = n 1 + ( ( n + 2 ) 2 − 1 ) = n 1 + ( n + 1 ) ⋅ ( n + 3 ) = n 1 + f ( n + 1 ) = n 1 + ( n + 1 ) 1 + f ( n + 2 ) = n 1 + ( n + 1 ) 1 + ( n + 2 ) 1 + ( n + 3 ) 1 + ( n + 4 ) 1 + ⋯ = 1 1 + ( 1 + 1 ) 1 + ( 1 + 2 ) 1 + ( 1 + 3 ) 1 + ( 1 + 4 ) 1 + ⋯ = 1 1 + 2 1 + 3 1 + 4 1 + 5 1 + ⋯